Combination of Amphotericin B and Terbinafine against Melanized Fungi Associated with Chromoblastomycosis - Deng, S. (2018)
Chromoblastomycosis (CBM) is a recalcitrant fungal skin disease which is difficult to treat, the infection leading to excessive proliferation of host tissues. Therefore, search for appropriate antifungal strategies is urgently needed. Our in vitro studies showed that combination of amphotericin B and terbinafine had synergistic effects against the majority of melanized fungi associated with CBM and similar infections, including Cladophialophora carrionii, C. arxii, Exophiala dermatitidis, E. spinifera, Fonsecaea monophora, F. nubica, F. pedrosoi, and Phialophora verrucosa, with a fractional inhibitory concentration (FIC) value ranging from 0.25 to 1. No synergistic interaction was found for Veronaea botryosa isolates. The results of FIC analysis were supported by response surface analysis using Bliss independence no-interaction model for the isolates tested. Our study suggests that amphotericin B, when combined with terbinafine, allows a significant reduction of MICs. This could provide an option for treatment of severe or unresponsive cases of CBM, particularly in cases due to species of Fonsecaea and Cladophialophora.